Age estimation of indian adults from orthopantomographs - Sudhanshu Saxena (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this study was to develop a method for estimating the chronological age of Indian adults based on the relationship between age and various morphological variables of canine teeth, obtained using orthopantomographs. Orthopantomographs of 120 selected patients were digitized, and radiographic images of the right maxillary canine in each case were processed using a computer aided drafting program. Pulp/tooth area ratio, pulp/root length ratio, pulp/tooth length ratio, pulp/root width ratio at the cemento-enamel junction level, pulp/root width ratio at midroot level, and pulp/root width ratio at the midpoint between the cemento-enamel junction and the midroot of the canine were calculated by measuring various features on the images. Pearson's correlation, multiple linear regression, one way analysis of variance (ANOVA), and Student's t-test were used for statistical analysis. Regression equations were developed to estimate age from morphological variables. The observed minus the estimated age in the total study sample ranged from -2.2 to +1.5 years, in males from -0.9 to +0.8 years, while in females it was from -1 to +0.8 years. Differences between observed and estimated ages of subjects were not statistically significant. In conclusion there is a linear relationship of pulp/root width ratio at mid-root level and pulp/tooth area ratio of the right maxillary canine with chronological age in the Indian population. Age of subjects can therefore be estimated with a good degree of accuracy using regression equations.